Targeted immunotherapy rescues pulmonary fibrosis by reducing activated fibroblasts and regulating alveolar cell profile - Jing Yan; Song-Yu Wang; Qi Su; Min-Wen Zou; Zi-Yue Zhou; Jian Shou; Yunlong Huo (Nature Communications)
Abstract Idiopathic pulmonary fibrosis (IPF) is a severe lung disease occurring throughout the world; however, few clinical therapies are available for treating this disorder. Overactivated fibroblasts drive abnormal fibrosis accumulation to maintain dynamic balance between inflammation and extracellular matrix (ECM) stiffness. Given pulmonary cell can regenerate, the lung may possess self-repairing abilities if fibrosis is removed via clearance of overactivated fibroblasts. The aim of this study was to evaluate the therapeutic activity of transient antifibrotic chimeric antigen receptor (CAR) T cells (generated via a novelly-designed lipid nanoparticle-messenger RNA (LNP-mRNA) system) and explore the regeneration mechanisms of lung in a male mouse model of bleomycin-induced pulmonary fibrosis. Here we found that fibrosis-induced ECM stiffening impaired alveolar epithelial cell compensation. The proposed LNP-mRNA therapy eliminated overactivated fibroblasts to rescue pulmonary fibrosis. The restored ECM environment regulated the cellular profile. The elevated plasticity of AT2 and Pclaf+ cells increased AT1 cell population via polarization. Apoe+ macrophages and increased numbers of effector T cells were shown to reestablish pulmonary immunity. Hence, LNP-mRNA treatment for fibrosis can restore pulmonary structure and function to similar degrees to those of a healthy lung. This therapy is a potential treatment for IPF patients.